(untitled) - Hjelmstad, Keith D. (New Jersey, 1997)
It provides a modern introduction to structural mechanics weaving a thorough treatment of basic continuum mechanics through the theories of beams and static stability theory. The book provides a solid prerequisite to the study of the finite element method and is suited for graduate and advanced undergraduate students in civil and mechanical engineering.
Keywords: Girders,Plates ( engineering ),Structural analysis ( engineering )